Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/nl8034338
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Solar Cells from P3HT and Silicon Nanocrystals

Abstract: We are reporting new hybrid solar cells based on blends of silicon nanocrystals (Si NCs) and poly-3(hexylthiophene) (P3HT) polymer in which a percolating network of the nanocrystals acts as the electron-conducting phase. The properties of composite Si NCs/P3HT devices made by spin-coating Si NCs and P3HT from a common solvent were studied as a function of Si NC size and Si NC/P3HT ratio. The open-circuit voltage and short-circuit current are observed to depend on the Si NC size due to changes in the bandgap an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
299
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(306 citation statements)
references
References 12 publications
4
299
0
2
Order By: Relevance
“…139 Other nanocrystals were also used to fabricate hybrid devices, for example silicon nanocrystals, CdS, ZnO, GaAs, and PbS. [140][141][142][143][144][145] Conjugated polymers other than P3HT were used to enhance the absorption. For example, the low band gap polymer PCPDTBT:CdSe tetrapods blends generated a power conversion efficiency of $3.2% [ Fig.…”
Section: Polymer-inorganic Hybrid Solar Cellsmentioning
confidence: 99%
“…139 Other nanocrystals were also used to fabricate hybrid devices, for example silicon nanocrystals, CdS, ZnO, GaAs, and PbS. [140][141][142][143][144][145] Conjugated polymers other than P3HT were used to enhance the absorption. For example, the low band gap polymer PCPDTBT:CdSe tetrapods blends generated a power conversion efficiency of $3.2% [ Fig.…”
Section: Polymer-inorganic Hybrid Solar Cellsmentioning
confidence: 99%
“…However, power conversion efficiencies of 1% have been shown recently with the first P3HT:Si-ncs blends. 8 Combined with an optimized charge transport and extraction at the electrodes, their efficiency is expected to increase.…”
Section: Conclusion and Implications For Hybrid And Organic Photovolmentioning
confidence: 99%
“…9 Prototype devices exhibited a relatively high open-circuit voltage of 0.75 V, 10 and power conversion efficiencies of around 1% have been achieved. 8 However, no detailed spectroscopic understanding has been available so far. Because of its current availability in crystalline, nanocrystalline, and amorphous forms, silicon serves as a model system with fundamental implications for various other hybrid or organic material systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that it can be also efficiently used for bulk-heterojunction formation when blended with conjugated polymers [17,18]. Natural micro/nano phase-separation between the polymer and the solid state Si-nc get the morphology/structure to obtain photogenerated carrier separation [17,18].…”
mentioning
confidence: 99%
“…It has been demonstrated that it can be also efficiently used for bulk-heterojunction formation when blended with conjugated polymers [17,18]. Natural micro/nano phase-separation between the polymer and the solid state Si-nc get the morphology/structure to obtain photogenerated carrier separation [17,18]. In addition, it is expected that Si-ncs with quantum confinement size effect may provide a significant boost in carrier generation efficiency from a phenomenon so called carrier multiplication [19][20][21][22].…”
mentioning
confidence: 99%